Fenomena Kekerasan dalam Berpacaran - Muhammad Jailani; Nurasiah Nurasiah (Journal of Gender and Social Inclusion in Muslim Societies, 2020)
This research departs from the basic assumption that Islam doesn’t recognize the terminology of ‘Dating’ and see it as forbidden, although it has becomed a contemporary practice and problem. This study of dating phenomenon which increasingly get acceptance and trendy among youth and adolescents as well as university’s students is to see the specific aspect of anomaly of violence happen in this relation by applying a critical gender approach. Sociologically, ‘dating’ is a reasonable form of expression and interaction based on trust and love. However, many went out of track to satisfy lust that bring out despair and regret. The phenomenon of dating is surrounded by complex problem for it can lead to a persimisiveness of free bodily and sexual contact and, furthermore, to a violation against the partner. This research is to know the context and condition of the violation between partners and its forms which is done with qualitative case study method. The respondents of the research is the students of North Sumatera UIN, of first till ninth semester. This study found that ‘dating’ is not only a matter of love and affection expression but also a kind of oppression relation, a motif to dominate, and even as a strategy for acquisition. This is to say that the substantial idea of the ‘dating’ as a process to be acquainted with prospective marriage partner is no longer true. As to the cause of the violence, i.e : a). Miscommunication; b). Jealousy toward the partner; c). Another affair; d). Disobey to dominated partners; e). Gender-biased behavior; and f). Tell a lie. At last, the type of violence ensured is ranged from non-violence (psychic, economic, sexual) to pyshical violence.